A plant tendril mimic soft actuator with phototunable bending and chiral twisting motion modes - Meng Wang (Nature Portfolio, 2016)
Plant tendrils are able to undergo both bending and chiral twisting motions but unfortunately synthetic mimics are unable to do this. Here the authors show a dual-layer polysiloxane-based liquid crystal soft actuator capable of two different 3D reversible transformations via light stimuli.